STRATEGI PENGEMBANGAN KAWASAN TAMBAKREJO KOTA SEMARANG DENGAN MENGGUNAKAN ANALISIS SWOT - Kurniawan, Ardi; Niam, Mohamad Faiqun; Rochim, Abdul (UNISSULA Semarang, 2023)
Tambakrejo is the northernmost sub-district in Gayamsari District, Semarang City, Central Java Province. This area is often hit by floods, especially when there is high tide or what is often called a tidal wave. Basically, this settlement emerged because there was a connection between three variables that influenced people to live in this area, namely the location or position in this area is part of quite important economic activity, because area activity is part of the economic activity of the city of Semarang. The aim of this research is to identify strengths, weaknesses, opportunities and threats using SWOT analysis, to develop a development strategy for the Tambakrejo area, Semarang City. Develop strategies and development programs for the Tambakrejo area, Semarang City The problems in this research will be analyzed descriptively qualitatively, IFAS (Internal Factors Analysis Summary) and EFAS (External Factors Analysis Summary) analysis as well as SWOT (Strengths Weaknesses Opportunities Threats) analysis to design development strategies. With these three analytical tools, it is hoped that we will be able to solve the problems to be studied. The strategy for the Tambakrejo area development project which was carried out using a SWOT analysis located in Quadrant I is a progressive strategy that produces a strategy for the development and development of the Tambakrejo area, the Semarang city government and BBWS Pamali Juana inventorying land for construction of river guardrails and PJUs, repair of TPS and IPAL, maintenance and routine maintenance of roads, channels and wastewater systems. So that the Tambakrejo area development project can be carried out effectively and efficiently.